Virtual education and clinical practices in final-year Peruvian dentistry students during COVID-19 pandemic - Cabrera-Tasayco, Fiorella del Pilar; Chávez-Méndez, Martín Andrés; Flores-Fraile, Javier; Peña-Soto, Claudio; De la Garza-Ramos, Myriam Angélica; Cano-Verdugo, Guillermo (Frontiers in Psychology, 2025)
IntroductionThe COVID-19 pandemic has significantly altered various sectors, with education being one of the most impacted. In Peru, the shift from in-person to virtual education was imperative due to the pandemic’s constraints. This study investigates the perception of virtual education and clinical practice among final-year dentistry students at a Peruvian institution during the SARS-CoV-2 pandemic.MethodsUtilizing a cross-sectional design, data were collected from 97 students via a survey assessing their experiences and expectations related to virtual learning and clinical skills. Instruments with dichotomous response scales measured students’ experiences with virtual education and their expectations regarding clinical practice.ResultsResults indicated that most students reported a moderate experience with virtual education, with similar moderate expectations for clinical practice. Statistical analyses revealed significant differences among experience levels and practice expectations, highlighting a disparity between students’ perceived skills and their confidence in applying these skills (p < 0.001).DiscussionThe study’s findings suggest that while virtual education has provided continuity, there remains considerable room for improvement in both the quality of online instruction and practical training. Enhancements in virtual teaching methods and additional support for clinical practice could better meet the needs of dental students. This study emphasizes the importance of ongoing evaluation and adaptation of virtual education strategies to address the evolving challenges and improve educational outcomes for future dental professionals.